PENGARUH PRICE BOOK VALUE (PBV), PRICE EARNING RATIO (PER), RETURN ON ASSET (ROA) TERHADAP RETURN SAHAM (Studi Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Septia Anggi Saputri; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThe purpose of this study was to determine the effect of the Price to Book Value, Price Earning Ratio , and Return On Asset on stock return in the sector consumer goods industry manufacturing companies. The independent variable in this study is the Price to Book Value, Price Earning Ratio, and Return On Asset, while the dependent variable in this study is the stock return. The type of research that is used is empirical research with the data used, namely secondary data obtained by searching and collecting annual report data obtained from the website. The population in this study is the sector consumer goods industry manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2018 with a total of 21 companies. The sample selection technique in this study was using purposive sampling, so that a sample of 18 companies was obtained. Using normality test, classic assumption test, multiple linear regression test and hypothesis test. The results of data analysis show : There is a positive influence on the Price to Book Value and Return On Asset, while the Price Earning Ratio have a negative effect on the stock return of the sector consumer goods industry manufacturing companies. Keywords: Price Book Value (PBV), Price Earning Ratio (PER) and Return On Asset (ROA), Stock Return.